2020
DOI: 10.3389/fgene.2020.00177
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Divergence and Relationship Among Opisthopappus Species Identified by Development of EST-SSR Markers

Abstract: Opisthopappus Shih is an endemic and endangered genus restricted to the Taihang Mountains that has important ornamental and economic value. According to the Flora Reipublicae Popularis Sinicae (FRPS, Chinese version), this genus contains two species (Opisthopappus longilobus and Opisthopappus taihangensis), whereas in the Flora of China (English version) only one species O. taihangensis is present. The interspecific phylogenetic relationship remains unclear and undefined, which might primarily be due to the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 72 publications
2
17
0
Order By: Relevance
“…promoted population divergence of plants in northern China flora, which has been indicated in previous results (Chai et al, 2020;Hou et al, 2014;Zhao et al, 2011). As phylogeographic information is useful in characterizing potential phylogeoregions, current genetic pattern of M. dioica and phylogeographical result in Opisthopappus suggests Taihang Mountains may be a potential phytogeographical boundary in Northern China (Chai et al, 2020). It is worth mentioning that we should be careful to estimate expansion and divergence time and population size changes from ABC model, as our data could not provide reliable distributions parameters and only provide a reference.…”
Section: Phylogeographic Structure and Demographic Historysupporting
confidence: 68%
“…promoted population divergence of plants in northern China flora, which has been indicated in previous results (Chai et al, 2020;Hou et al, 2014;Zhao et al, 2011). As phylogeographic information is useful in characterizing potential phylogeoregions, current genetic pattern of M. dioica and phylogeographical result in Opisthopappus suggests Taihang Mountains may be a potential phytogeographical boundary in Northern China (Chai et al, 2020). It is worth mentioning that we should be careful to estimate expansion and divergence time and population size changes from ABC model, as our data could not provide reliable distributions parameters and only provide a reference.…”
Section: Phylogeographic Structure and Demographic Historysupporting
confidence: 68%
“…However, traditional SSR development methods are labour intensive [ 13 ]. At present, SSR markers developed by high-throughput sequencing are reliable and effective [ 19 , 38 41 ]. Genomic SSRs have not been developed thus far in V. amoena , and a new set of highly polymorphic SSR markers was successfully developed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that the trinucleotide SSRs in the V. amoena genome are mainly located in exon regions. The frequent distribution of trinucleotide repeats in coding regions indicates the effects of selection and evolution [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The markers used in the previous researches might reveal less genetic information than the markers used in this study that obtained across the whole genome of Opisthopappus . The EST-SSR markers developed from the transcriptome data also divided Opisthopappus populations into two clusters [ 43 ].…”
Section: Discussionmentioning
confidence: 99%